A Partial Defence of Descriptive Evidentialism About Intuitions: A Reply to Molyneux. (January 2017) - Andow, James
Abstract: Bernard Molyneux presents some new arguments against descriptive evidentialism about intuitions. Descriptive evidentialism is the thesis that philosophers use intuitions as evidence. Molyneux's arguments are that: (1) the propositions that intuition putatively supports are treated as having a degree and kind of certainty and justification that they could not have got from being intuited; (2) intuitions influence us in ways we cannot explain by supposing we treat them as evidence; and (3) certain strong intuitions that persuade us of their contents are treated as inadmissible in the context of justification. This article presents a partial defence of descriptive evidentialism against these new arguments.